2021
DOI: 10.1002/ejic.202100654
|View full text |Cite
|
Sign up to set email alerts
|

Halide Ion Migration and its Role at the Interfaces in Perovskite Solar Cells

Abstract: Lead-halide perovskite solar cells (PSCs) based on unusual semiconductors made with ions, have shown impressive improvement in photovoltaic performance in few years exceeding nowadays 25 % power conversion efficiency. However, PSCs suffer from a lack of stability and show significant hysteresis in current-voltage curves, which are impeding commercialization. We confirmed the importance of halide ion migration in the hysteresis effect which has direct consequences on device efficiency. Using impedance spectrosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 89 publications
1
13
0
Order By: Relevance
“…The equilibrium charged vacancy concentration is predicted to exceed 0.4 % at room temperature 66 . The J-V hysteresis is also measured under dark conditions at room temperature both in hybrid and inorganic perovskite solar cells, which suggests ionic conduction to take place in dark 67 .…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…The equilibrium charged vacancy concentration is predicted to exceed 0.4 % at room temperature 66 . The J-V hysteresis is also measured under dark conditions at room temperature both in hybrid and inorganic perovskite solar cells, which suggests ionic conduction to take place in dark 67 .…”
Section: Discussionmentioning
confidence: 88%
“…Another notable observation is the mobility of Cs + in the various device architecture studies in this work (Tables S1, S2, S3). It has been suggested that if amount of Cs + is higher than 15%, the α-CsPbI 3 phase converts to δ-CsPbI 3 phase, which lead to degradation 36,37 and a J-V hysteresis in the IHPs 67 . When compared to a mobile organic counterpart, e.g., MA + present in organic-inorganic hybrid halide perovskites, the elemental peak of Cs + in our work is smooth and the slight changes in concentration confirms its less mobile nature than MA + and FA + 46,61 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As the current‐voltage ( J‐V ) curves and capacitive responses of PSCs are connected, the analysis of the capacitive responses will be helpful to understand the nature of charge distribution within the device and also the kinetics of the charge transport/migration processes. Capacitance spectroscopy has been employed to investigate the degradation mechanism in PSCs, [20,21] as well as provides the knowledge of ionic migration and origin of the anomalous J‐V hysteresis observed in PSCs [22] . Such information is useful for the quantitative evaluation of electrical parameters of PSCs which have a prominent role in the device performance [23–26] …”
Section: Introductionmentioning
confidence: 99%